Prevalence of Accident Occurrence Among Scientific Laboratory Workers of the Public University in Lebanon and the Impact of Safety Measures - Inaam M. Nasrallah; Assem K. El Kak; Lina A. Ismaiil; Rihab R. Nasr; Wafa T. Bawab (Elsevier, 2022)
Background: Workers are exposed to several risks in academic laboratories due to the presence of potentially hazardous substances. The main objective of this study was to assess the prevalence of accident occurrence and associated risk factors among laboratory workers at the scientific laboratories of the public university in Lebanon and the impact of safety measures training and availability. Methods: In this observational study, a survey was conducted for one year in scientific laboratories at faculties of the public university. Results: Among the participants (N = 220), 45.0% have had accidents; the main cause was exposure to chemicals (73.7%) and more specifically by inhalation (45.4%). Females (85.9%) were more exposed to accidents than males. Laboratory workers with a master's degree, a full-time schedule, and more than ten years of experience were significantly more exposed to accidents (p < 0.05). A significant association was found between accident occurrence and training on management of hazardous products (p = 0.044), risks related to workplace (p = 0.030), eyewash and emergency shower (p < 0.001), first aid (p = 0.012), and facial protection availability (p = 0.019). In spite of the lack of safety culture and efficient training on laboratory safety, participants have shown a very good perception regarding safety measures to be applied in case of work accidents. Conclusion: Based on our findings, the prevalence of accident occurrence is elevated among lab workers at the public university. The impact of regular training on laboratory safety preventive measures is of great importance to ensure the efficiency of occupational health and safety in scientific laboratories.